Review of the leafhopper genus Oniella Matsumura (Hemiptera: Cicadellidae), with description of a new species from China - Min, Gao; Zhang, Yalin (Zootaxa, 2013)
The genus Oniella Matsumura 1912 is reviewed and seven species from China are recognized, including a new species, O. shaanxiana sp. nov., a new synonym, O. flavomarginata, syn. nov. and a new combination, O. albula (Cai & Shen, 1998) n. comb. transferred from Sophonia. O. excelsa (Melichar) is removed from this genus. The seven species are described and illustrated in detail, and a key to all species of the genus is provided.